1999
DOI: 10.1002/(sici)1097-4628(19990919)73:12<2437::aid-app12>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Urea-formaldehyde crosslinked starch and guar gum matrices for encapsulation of natural liquid pesticide [Azadirachta Indica A. Juss. (neem) seed oil]: swelling and release kinetics

Abstract: Polymeric granules were prepared by matrix encapsulation containing 20, 35 and 50% (w/w) of natural liquid pesticide viz., Azadirachta Indica A. Juss. (neem) seed oil (NSO) per dry weight of urea formaldehyde crosslinked starch (UF-St), guar gum (UF-GG) and UF-(St ϩ GG) matrices. Results of swelling and cumulative release kinetics are presented at 35°C for these matrices. The static dissolution experiments have been carried out at 35°C for seven days. The percentage cumulative release kinetic data have been an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Perhaps the main effect of dietary fibers on bile acids in the small intestine is to decrease the efficiency of the enter hepatic circulation resulting in a greater fecal excretion. Probably guar gum with increasing viscosity in digestive system is able to decrease uptake rate of substances and disturbance in reuptake of bile acids and can therefore have positive effect on decrease of glucose, cholesterol, triglyceride and LDL-C of blood, but the mechanism is not known and clear (Moriceau et al, 2000, Kulkarni et al, 1999, Soppimath et al, 2000. The biological activity of guar gum seems to depend mainly on its capacity to increase the viscosity of digest in the upper gastrointestinal tract (Rideout et al, 2008, Sangamesh et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the main effect of dietary fibers on bile acids in the small intestine is to decrease the efficiency of the enter hepatic circulation resulting in a greater fecal excretion. Probably guar gum with increasing viscosity in digestive system is able to decrease uptake rate of substances and disturbance in reuptake of bile acids and can therefore have positive effect on decrease of glucose, cholesterol, triglyceride and LDL-C of blood, but the mechanism is not known and clear (Moriceau et al, 2000, Kulkarni et al, 1999, Soppimath et al, 2000. The biological activity of guar gum seems to depend mainly on its capacity to increase the viscosity of digest in the upper gastrointestinal tract (Rideout et al, 2008, Sangamesh et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported similar loading values for the encapsulation of pesticides using biopolymers as matrices, with microspheres based on cellulose derivatives loaded with a commercial herbicide presented loading values in the range of 8-11%, 26 while alginate beads loaded with a natural pesticide Neem (Azadirachta Indica A. Juss) showed loading values of 10 to 30%. 21 …”
Section: Resultsmentioning
confidence: 99%
“…Although having widespread use as controlled-release systems in medicine and pharmacy, nanoparticles have found little usage in agriculture, particularly as carriers for pesticides. [21][22][23] In another approach, a new chitosan/alginate-based matrix for biodegradable pesticide release has been reported. 23 In a previous study, chitosan/cashew gum microspheres were developed for encapsulation of DDVP (dimethyldivinyl chloride phosphate) aiming at larvae control.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new technology using modified natural polymers for fertilizer and drug release devices in agroindustries and medicine applications exhibited better viability than the use of synthetic polymers, since these are known to create some environmental concern, starch hydrophilic and capable of absorbing water and swelling dramatically in aqueous solution and low cost . In order to improve starch properties, starch is graft copolymerized with different materials.…”
Section: Introductionmentioning
confidence: 99%